2014
DOI: 10.11564/28-1-503
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Unmet Need for Modern Contraception and Reasons for Non-use among Married Women in Rural Areas of Burkina Faso

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
79
3
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(107 citation statements)
references
References 29 publications
(19 reference statements)
21
79
3
4
Order By: Relevance
“…Thus, the prevalence of unmet need for limiting increases with the number of children. This result is in agreement with other studies conducted using DHS (Assefa and Fikrewold 2011;Kisaakye 2013;Adebowale and Martin 2014).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Thus, the prevalence of unmet need for limiting increases with the number of children. This result is in agreement with other studies conducted using DHS (Assefa and Fikrewold 2011;Kisaakye 2013;Adebowale and Martin 2014).…”
Section: Discussionsupporting
confidence: 93%
“…This, in turn, improves their knowledge and practice of contraception. This finding is in accordance with a study result of Westoff (2012) and Adebowale and Martin (2014), which concluded that women with unmet need are less educated than women using a modern contraception.…”
Section: Discussionsupporting
confidence: 92%
“…6 Persetujuan suami terhadap keluarga berencana adalah faktor protektif kejadian unmet need untuk metode kontrasepsi modern (OR=0,858;CI=0,756 -0,975;p=0,019). 7 Palamuleni dalam penelitiannya menunjukkan bahwa faktor utama yang mempengaruhi penggunaan metode kontrasepsi adalah usia, persetujuan pasangan mengenai program keluarga berencana, diskusi dengan pasangan, jumlah anak yang hidup, status pekerjaan, pendidikan dan kunjungan ke pusat kesehatan. 8 Fertilitas dan keterlibatan suami adalah determinan yang paling penting dalam hal penggunaan metode kontrasepsi pasangan.…”
Section: Pendahuluanunclassified
“…It was seemed significantly lower in the household for the use with husbands' approval than without. 12 In Cairo, one of risk factors of unmet need was husbands disapproval in using contraception with OR=2.96; 95% CI=1.47-5.97. 13 In six cities in Iran was also mentioned that family disapproval also became the reason of the high unmet need.…”
Section: Factors Associated With Unmet Needmentioning
confidence: 99%
“…The purpose is to prevent and reduce the unmet need of modern contraception. 12 Intervention to reduce unmet need is relevant to increase the use of contraception in India and four countries in East Africa, by supplying high quality resources and infrastructure to support FP services such as the availability of private room which assure visual and auditory privacy in counseling, the increase of contraception access in rural, the increase of health officers motivation related to FP program, free contraception supply, and many other. Besides, generally the FP program provider is supervised routinely.…”
mentioning
confidence: 99%